Competitiveness Analysis of Lampung Province Coffee: RCA and RSCA Approach - Kusmaria; Sudiyo; Edy Humaidi (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2025)
Lampung province is one of the coffee production centers in Indonesia. The coffee industry in Lampung is a significant contributor to the local economy, with its products being sent to various regions in Indonesia and even abroad. However, it has yet to be discovered whether the coffee products produced can compete with those from other regions. This research aims to analyze the competitiveness of coffee in Lampung province. This research was conducted in Lampung Province. This location was chosen purposively, taking into account that this area is a coffee production center and is the area with the second-highest coffee production in Indonesia. This research uses secondary data in the form of time series data over a period of 5 years (2018-2022). The analytical tool used to analyze the comparative competitiveness of coffee uses the Revealed Comparative Advantage (RCA) and Revealed Symmetric Comparative Advantage (RSCA) methods. The research results show that the coffee commodity in Lampung Province over the last 5 years has had high competitiveness, as seen from the RCA value > 1 and the RSCA value > 0.